Provision of milkfish (Chanos chanos) waste flour as a commercial feed substitute for feed consumption and carcass percentage of Japanese quail (Coturnix coturnix japonica) - Bayu Dwi Saputra; Mirni Lamid; Sunaryo Hadi Warsito; Sri Hidanah; Emy Koestanti Sabdoningrum; Widya Paramita Lokapirnasari (Universitas Airlangga, 2024)
The purpose of this research was to determined the substitution of milkfish (Chanos chanos) waste flour can increase feed consumption and carcass percentage of Cortunix cortunix japonica. There are 20 quails (Coturnix coturnix japonica) of four treatments and five replications. Each treatment consisted by five quails. The treatment consisted of P0 with commercial feed 100%, P1 with commercial feed 98% + milkfish waste flour 2%, P2 with commercial feed 96% + milkfish waste flour 4%, and P3 with commercial feed 94% + milkfish waste flour 6%. Based on the results of the Analysis of Variance (ANOVA) there was significantly different (p<0.05) on feed consumption and carcass percentage. It can be concluded the substitution of commercial feed with milkfish (Chanos chanos) waste flour can increase feed consumption and carcass percentage of Japanese quail.